The problems of Eastern Orthodox church buildings of historical value - changing uses over the years = Problemy zabytkowych obiektów cerkiewnych - zmiana funkcji użytkowych na przestrzeni lat - Jarocka-Mikrut, Aleksandra; Gleń, Piotr (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
There are many Eastern Orthodox church buildings throughout the Lublin Province. Over the years, these architectural objects have undergone multiple transformations, both in terms of changing religious denominations and rituals and also adaptation to new functions, such as warehousing. This article classifies and presents the transformations carried out in selected Eastern Orthodox churches in the Lublin province.
Keywords: cerkiew; obiekty zabytkowe; adaptacja; województwo lubelskie; Eastern Orthodox church; adaptation; transformation; Lublin province